The place of free speech in Internet governance debate - Antonyuk, Artem (AoIR Selected Papers of Internet Research, 2016)
I propose a neo-institutional framework for addressing the role of ideas and discourses at the Internet Governance Forum (IGF) with a focus on discussions of freedom of speech. Accordingly, the IGF is seen as an organization exploiting the institutional opportunities for behavior. While organizations such as IGF claim to provide a forum for open discussions of relevant topics, they still draw on the institutional context. It may be expected that different culturally specific notions of free speech are contested in discussions at IGF which are supported by institutionalized discourses (e.g. legal and regulative). Serving as an outline of a framework for an empirical study, this paper is intended to provoke discussions rather than present any conclusions.